Self-investigation and subjectivity in Montaigne’s Essays - Ludwig, Carlos Roberto (Revista de Letras, 2014)
Montaigne’s creation of the Essays, as a renewing literary form, caused great impact in his age. Montaigne aims at representing the subjectivity through a new literary form, whose traits are remarkably the use of language without being stuck to rhetorical conventional forms, an open form which could depict subjectivity. Besides that, writing the Essays turns out to be self-writing, in a language and form which contain subjectivity, thoughts, ideas, inner floatation. Montaigne considered that human behavior as well as the inner dimensions of the self were aesthetic contents which needed an open form, free of the chains of the conventional rhetoric. Because of that, he created the Essay in order to represent and investigate the deepest dimensions of the self. In this article, I will analyze some elements from the essays, wherein Montaigne goes deeper into the twist and turns of conscience, feelings and thought, suggesting nuances and tones of subjectivity. I will discuss how Montaigne represents subjectivity, detailing obscure and uncontrolled elements of the thought and sensations, as well as contradictions, floatation, ambiguities inherent to subjectivity.